Feasibility of audio-visual teaching materials to support tennis learning - Septian Raibowo; Abi Fajar Fathoni; Sapto Adi (Jurnal Keolahragaan, 2022)
This study aims to produce court tennis audio-visual teaching materials and determine the effectiveness of audio-visual teaching materials to support court tennis learning. This research is development research with stages: needs analysis, data collection, product development, expert validation, product testing, product revision, and evaluation. The subjects of this study were taken using a random sampling method, amounting to 47 people. The instruments used to collect data were questionnaire sheets, expert validation sheets and further tests were analyzed using descriptive statistics. Seeing the effectiveness of the product using an experimental design with the format "one group pretest-posttest design", which does not use a comparison class but has used an initial test so that the magnitude of the effect due to the use of the product can be known with certainty. The results showed that the results of the validation of media experts, learning experts material experts were very valid and the validation of evaluation experts was quite valid. The quality of the product from the large-scale test is categorized as high. The results of the product effectiveness test show a significant and efficient increase in learning outcomes and have a fairly high attractiveness in supporting court tennis learning.